O Castelo de Franz Kafka: uma leitura sob a perspectiva do poder microfísico - Michelle Evangelina Fonseca de Campos (2017)
The present work consists of an attempt to approach the links between power relations found in the novel The Castle, by Franz Kafka, and the microphysics of power perspective, presented by Michel Foucault. According to this view, individuals are not inert targets subject to power that comes from a center that exclusively holds and wields it, without offering the possibility of resistance. In The Castle, the protagonists struggles are not limited to being against the insane bureaucracy of a totalitarian state, and, most of times, they are not against official government agencies. The microphysics perspective proposes an approach according to which power is an effect generated by force relations; it is not susceptible of being owned and it is not wielded without facing resistance, it is anonymous and dispersed among society. The villagers deeds coercively work towards a domination that functions through the individuals relation to their own identity, objectifying them and making them subject. Thus, this work intends to address the aspect whereby the protagonist is oppressed not only by official procedures that prevent him of succeeding in its goals, but also by the community members and how this aspect takes place in time and space.